Air Pollution Exposure Impairs Airway Epithelium IFN-β Expression in Pre-School Children - Bonato, Matteo; Gallo, Elisa; Turrin, Martina; Bazzan, Erica; Baraldi, Federico; Saetta, Marina; Gregori, Dario; Papi, Alberto; Contoli, Marco; Baraldo, Simonetta (Frontiers in Immunology, 2021)
Introduction Air pollution is a risk factor for respiratory infections and asthma exacerbations. We previously reported impaired Type-I and Type-III interferons (IFN-β/λ) from airway epithelial cells of preschool children with asthma and/or atopy. In this study we analyzed the association between rhinovirus-induced IFN-β/λ epithelial expression and acute exposure to the principal outdoor air pollutants in the same cohort. Methods We studied 34 children (17asthmatics/17non-asthmatics) undergoing fiberoptic bronchoscopy for clinical indications. Bronchial epithelial cells were harvested by brushing, cultured and experimentally infected with Rhinovirus Type 16 (RV16). RV16-induced IFN-β and λ expression was measured by quantitative real time PCR, as was RV16vRNA. The association between IFNs and the mean exposure to PM10, SO2 and NO2 in the day preceding bronchoscopy was evaluated using a Generalized Linear Model (GLM) with Gamma distribution. Results Acute exposure to PM10 and NO2 was negatively associated to RV16-induced IFNβ mRNA. For each increase of 1ug/m3 of NO2 we found a significative decrease of 2.3x103 IFN-β mRNA copies and for each increase of 1ug/m3 of PM10 a significative decrease of 1x103 IFN-β mRNA copies. No significant associations were detected between IFN-λ mRNA and NO2 nor PM10. Increasing levels of NO2 (but not PM10) were found to be associated to increased RV16 replication. Conclusions Short-term exposure to high levels of NO2 and PM10 is associated to a reduced IFN-β expression by the airway epithelium, which may lead to increased viral replication. These findings suggest a potential mechanism underlying the link between air pollution, viral infections and asthma exacerbations.